Manajemen Dakwah Sosial di Madrasah Dalam Membangun Literasi Digital Beretika - Ismul Hadi; Maliki (Mudabbir: Jurnal Manajemen Dakwah, 2025)
The development of digital technology has brought significant changes to the learning patterns, social interactions, and media behavior of students in madrasahs. This condition demands adaptive management of Islamic education through the integration of social dakwah management and ethical digital literacy. This study aims to conceptually examine the role of social dakwah management in strengthening ethical digital literacy to shape students' character in the digital era. The method used is a literature study by reviewing various credible and up-to-date academic sources, both books and journal articles relevant to Islamic education, dakwah, and digital literacy. The study results indicate that digital literacy from the perspective of Islamic education emphasizes not only technical mastery of technology but also ethical, critical, and spiritual aspects based on Islamic moral values. The success of implementing this strategy is greatly influenced by the role of educators as digital da'wah agents, the support of madrasa leadership, and parental involvement in monitoring and guiding the use of digital media. The sustainable formation of students' digital ethics relies on the synergy of these three elements.